A new challenge for dental education : generation Z = Un nuevo reto para la educación odontológica : generación Z - López Santacruz, Hiram Daniel
A new cohort, known as "Generation Z", is nowadays studying Health Careers. These students were born between 1996 and 2012, and currently at year 2022, have between 18 and 26 years. It is necessary to comprehend their characteristics and behaviors, for a better understanding of how they learn, what do they expect from education and how to improve their academic development and potential. Generation Z is considered as the most diverse, and it requires a closer mentorship from teachers, who must be ready to help students to manage their time and resources efficiently. It is worth mentioning that Gen Z information about their professional performance is still preliminary, because they are currently studying their University programs. Thus, it will be interesting to further analyze the behavior of Generation Z in Dental Education.